Comparison of Wedding Donation in Hungarian Law and Mahr in Islamic Law - Baranyi, Emese Zsuzsanna (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2019)
The following study compares the Hungarian regulation of wedding donations in different ages with the legal institution of mahr in Islamic law, which continues to be considered an obligatory element of Islamic marriage to the present day. The mahr, which has to be paid by the groom to the bride, has a living tradition in today's Muslim communities. Older Hungarian regulations, mainly based on civil law proposals, drafts and articles, include the concept of the wedding gift (that the groom gave to the bride), the dowry (that the woman brought to the marriage) and the dos (reward for the loyal wife). Currently there is no legal institution similar to the mahr in Hungarian family law, as current Hungarian law treats parties to be married and spouses as equal parties in all aspects. However, in the past, wedding donations regulated by law were seen as essential elements of marriage, and they played a significant role in Hungarian society until the middle of the 20th century, with their purpose and function being almost the same as that of the mahr.